Efficacy of acellular xenogeneic dermal matrix graft in the treatment of multiple gingival recessions: systematic review and meta-analysis - Costa, Matheus Souza Campos (2024)
Objective: This study aimed to compare the efficacy of acellular xenogeneic dermal matrix graft (AXDM) compared to connective tissue graft (CTG) in treating multiple gingival recessions. Materials and methods: A systematic search of electronic databases was conducted to identify randomized clinical trials (RCTs) that compared AXDM and CTG. The selected studies were subjected to bias risk assessment, data extraction, and meta-analyses. Parameters such as gingival recession height, width, mean percentage of root coverage, and complete root coverage were analyzed. Results: Seven RCTs involving 146 patients were included. The meta-analyses indicated that CTG was statistically superior to AXDM in reducing gingival recession height at the final follow-up (mean difference: -0.104 mm, 95% confidence interval [CI]: -0.180-0.028, p = 0.008) and width at the final follow-up (mean difference: -0.285 mm, 95% CI: -0.541-0.030, p = 0.029). CTG also demonstrated a significantly higher mean percentage of root coverage at the 6-month follow-up (difference in means: -2.761 mm, 95% CI: -4.932-0.590, p = 0.013) and a higher percentage of complete root coverage at the 6-month follow-up (odds Ratio [OR]: 0.598, 95% CI: 0.4-0.892, p = 0.012) compared to AXDM. However, there was no significant difference in the number of teeth with complete root coverage between CTG and AXDM (OR: 1.610, 95% CI: 0.983–2.636, p = 0.058) and aesthetic outcomes (mean difference: 0.148, 95% CI: -0.277-0.573, p = 0.494). Conclusions: CTG is more effective than AXDM in treating multiple gingival recessions. This is evidenced by significant reductions in gingival recession height and width, a higher mean percentage of root coverage, and a greater percentage of complete root coverage at the 6-month follow-up. Clinical relevance: In some clinical situations an alternative to CTG is required for the treatment of multiple gingival recessions. AXDM, despite presenting clinical outcomes that are not as satisfactory as CTG, can be used for this purpose.